Effect of cord blood mononuclear stem cells transplantation on the improvement restoration of decreased myocardial contractility - A. Usenko; A. Yakushev; A. Matyaschuk; M. Kostilev; V. Onishchenko (Ukrainian Journal of Cardiovascular Surgery, 2017)
The existing methods of treating heart failure (HF) do not completely solve the problem, so the world is searching for alternative approaches. One of the newest methods is cell therapy. A number of studies have demonstrated the perceptivity of using mononuclear cord blood stem cells (MCB SC). However, the effect of MCB SC on myocardial contractility remains poorly studied.Aim of study. To analyze the changes in contractility of the myocardium and parameters of intracardiac hemodynamics in patients with heart failure after transplantation of mononuclear stem cells of umbilical cord blood.Materials and methods. We have analyzed the results of treatment of 20 patients with refractory HF, who underwent MCB SC transplantation in the schedule of conservative treatment.Discussion. In the post-transplant period, a statistically significant increase in the left ventricular ejection fraction was registered, mainly due to a decrease in the end systolic index, as well as an improvement in the values of the local contractility index at the follow-up period up to 9 months.Conclusions. The use of the cellular preparation “Cryopreserved human umbilical cord blood” in the schedule of con-servative treatment of the refractory HF made it possible to partially restore the reduced contractile function of the myocar-dium and to increase the effectiveness of traditional schemes of conservative treatment of HF in terms of up to 9 months.